The 5S Culture Implementation in PT Indonesia Kendaraan Terminal Tbk Office Area - Neni Haqnanda Dimi; Noeroel Widajati; Lydia Elsa Sinta; Fitri Yatulaini; Gita Rizki Amaliya; juliana Jalaludin; Ahsan Ahsan (Universitas Airlangga, 2022)
Background: One of the Occupational Safety and Health implementation programs to minimize work accidents and occupational diseases is the application of 5S culture (Sort, Set in Order, Shine, Standardize, and Sustain). It aims to create a new and positive energy for the workers and maintain the better work environment. PT Indonesia Kendaraan Terminal (IKT) Tbk is a subsidiary of PT Pelabuhan Indonesia II which is engaged in vehicle import-export services. At office area, there are stack of papers, unneatly box and work station. Objectives: The purpose of this study is to assess the 5S culture implementation. Methods: This study is an observational study conducted at PT Indonesia Kendaraan Terminal Tbk which is located at Jalan Sindang Laut No. 100, Cilincing, North Jakarta, 14110 in February until March 2021. Data collection was done by observation and 5S form assessment based on the guidelines according to Pertamina's 2011 command letter. Results: In driving factors, 5S organizational has not yet formed but had been socialized. In addition, the results of the 5S assessment, at sort, set in order, shine, and sustain aspects are in the enough category. Meanwhile the standardize aspect in not good category. Conclusions: PT Indonesia Kendaraan Terminal Tbk has not maximally implemented the 5S culture caused by changes in the organizational structure, the company prioritizing in operational services. In addition, the application of 5S culture is only as a branding so it's not considered as important thing in the work process.